99mTc-Hynic-TOC imaging in the diagnostic of neuroendocrine tumors - Liepe, Knut; Becker, Andreas (World Journal of Nuclear Medicine, 2018)
The aim of this study was to assess the potential of 99mTc-Hynic-TOC imaging in the primary diagnosis and follow-up of midgut neuroendocrine tumors (NETs). In comparison to 111In-octreotide, 99mTc-Hynic-TOC has a higher imaging quality and leads to a lower radiation absorption in patients. 99mTc-Hynic-TOC was used for assessing primary diagnosis (n = 14) and during follow-up (n = 17) in patients with NETs. The scintigraphic findings were compared with computed tomography scans and follow-up. In 31 patients, 34 somatostatin receptor scans using 99mTc-Hynic-TOC were performed. The primary diagnoses were midgut NET. The scintigraphy was true positive in 17 patients, true negative in 9, false negative in 4, and false positive in 1. From these data, a sensitivity of 81%, specificity of 90%, positive predictive value of 94%, and negative predictive value of 69% were calculated. In summary, 99mTc-TOC represents a useful radiotracer in imaging SSTR-expressing tumor lesions with slightly higher sensitivity, higher imaging quality, and lower radiation exposure for patients compared to 111In-octreotide. A 1-day double-acquisition protocol should be used to reduce false-positive findings of the gut.
Keywords: 99mTc-Hynic-TOC imaging; neuroendocrine tumor; octreotide; somatostatin receptor